2019
DOI: 10.1177/1557988319847088
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Pre-Exposure Prophylaxis Self-Efficacy Among Men Who Have Sex With Men

Abstract: This research examines the level of pre-exposure prophylaxis (PrEP) self-efficacy among HIV-negative men who have sex with men (MSM) in China and identifies the influencing factors associated with the level of PrEP self-efficacy in terms of social-demographic characteristics and social psychological factors. The data were gathered from a baseline assessment of a longitudinal randomized controlled intervention trial. From April 2013 to March 2015, nonprobability sampling was used to recruit HIV-negative MSM at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…agreement with previous research by Dou et al (2019) and Klein (2014), which showed that individuals with a higher degree of HIV prevention-related knowledge, including PrEP and condom use, also demonstrate a higher level of HIV prevention self-efficacy, which may potentially lead to decreased rates of HIV. Another possible explanation for this finding is that men who do not feel comfortable discussing PrEP may also be less likely to acknowledge other components of sexual health and thus may be less likely to be aware of behaviors that place them at risk of acquiring HIV or less likely to discuss sexual risk-taking behaviors in general.…”
Section: Discussionsupporting
confidence: 92%
“…agreement with previous research by Dou et al (2019) and Klein (2014), which showed that individuals with a higher degree of HIV prevention-related knowledge, including PrEP and condom use, also demonstrate a higher level of HIV prevention self-efficacy, which may potentially lead to decreased rates of HIV. Another possible explanation for this finding is that men who do not feel comfortable discussing PrEP may also be less likely to acknowledge other components of sexual health and thus may be less likely to be aware of behaviors that place them at risk of acquiring HIV or less likely to discuss sexual risk-taking behaviors in general.…”
Section: Discussionsupporting
confidence: 92%
“…On the basis of our previous research [ 5 , 40 ], all questions used to describe factors that perceived susceptibility, severity, benefits, barriers, and medication self-efficacy were measured with five-point Likert questions. The measurement problem details of the six dimensions of HBM are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy refers to the level of a person’s confidence in his or her ability to perform a behavior successfully. The higher the self-efficacy is, the better a disease-preventive behavior is [ 38 , 39 , 40 , 41 ]. Accordingly, we made the following assumption about the prediction relationship between the self-efficacy and HIV-preventive behaviors of MSMs.…”
Section: The Hbm Modelmentioning
confidence: 99%
“…One study showed the median adherence rate of daily oral PrEPin clinical trials was 64.29%, the main objective factor in non-adherence was forgetting to take the medicine [45], LAI PrEP may improve PrEP ad-herence to some extent and may further reduce the incidence of HIV. Qu, et al [46]. explored the impact factors to the low-level PrEP self-efficacy (Self-efficacy, as the determinant of individual behavior, is also the center of individual factors that often influences the choice and continuation of individual behavior [47] in China, age and anxiety score were negatively related to PrEP self-efficacy, AIDS-related knowledge and PrEP-related motiva- One study [27] showed that the top 2 reasons for willingness to use PrEP are "efficacy to sexual health" and "problems using condoms" and the top 3 reasons for unwillingness to use PrEP are "concern about side effects, long dose schedule", "confidence in protecting themselves" and "cost and atigma".…”
Section: Discussionmentioning
confidence: 98%